Tinjauan Ekonomi Islam Terhadap Upah Mandor Pada PT. Kartika Hijau Lestari - Fitrah Ilham Ramdhan; Mawaddah Irham (Journal of Islamic Economics and Finance, 2024)
The aim of the research is to determine the system for determining wages for palm oil plantation foremen and the forms of Islamic economic values at PT Kartika Hijau Lestasi Serafoh plantation, Sangga Lima village, Gebang district. Langkat Regency,. North Sumatra. The method used is descriptive qualitative with a data reduction model, data presentation and drawing conclusions. The research results show that the palm oil plantation wage system in determining wages is in accordance with the principles of Islamic Economics, because the oil palm plantation owner discusses in advance the amount of wages that will be given. Regarding payment procedures, oil palm plantation owners do not delay giving wages, wages are given directly to workers after the workers have finished their work. The wage system for palm oil plantations meets the value of justice, because in providing wages to workers there are differences in wages for each type of work carried out. However, the wages paid do not meet the appropriate value, because the wages set cannot meet the living needs of workers even though the wages paid are in accordance with Langkat Regency UMK standards.